Pengaruh Lokasi Dan Promosi Terhadap Keputusan Pembelian Tenun Ikat Pada Kelompok Wanita Penenun Mbolaso Di Kelurahan Hewuli, Kabupaten Sikka - Pareira, Stefanus Genosius Selong; Yosef Tonce; Pareira, Rosalina Andriyani Ebang (Universitas Nusa Nipa Maumere, 2026)
This study examines purchasing decisions for ikat weaving at the Mbolaso Women Weavers Group Studio in Hewuli Village, Sikka Regency. The study aims to describe purchasing decisions, promotion, and location, and to analyze the influence of promotion and location on purchasing decisions partially and simultaneously. The study involved 70 consumers as samples selected using non-probability sampling. The researcher collected data through questionnaires and analyzed it using descriptive statistics and multiple linear regression with t-tests and F-tests. The results showed that promotion and location had a significant effect on purchasing decisions, both partially and simultaneously. The promotion and location variables explained 49.9% of the variation in purchasing decisions, while the rest was influenced by other factors outside the scope of this study.